Human Lung Cancer Risks from Radon - Part II - Influence from Combined Adaptive Response and Bystander Effects - a Microdose Analysis - Bobby E. Leonard; Richard E. Thompson; Georgia C. Beecher (SAGE Publishing, 2011)
In the prior Part I, the potential influence of the low level alpha radiation induced bystander effect (BE) on human lung cancer risks was examined. Recent analysis of adaptive response (AR) research results with a Microdose Model has shown that single low LET radiation induced charged particles traversals through the cell nucleus activates AR. We have here conducted an analysis based on what is presently known about adaptive response and the bystander effect (BE) and what new research is needed that can assist in the further evaluation human cancer risks from radon. We find that, at the UNSCEAR (2000) worldwide average human exposures from natural background and man-made radiations, the human lung receives about a 25% adaptive response protection against the radon alpha bystander damage. At the UNSCEAR (2000) minimum range of background exposure levels, the lung receives minimal AR protection but at higher background levels, in the high UNSCEAR (2000) range, the lung receives essentially 100% protection from both the radon alpha damage and also the endogenic, spontaneously occurring, potentially carcinogenic, lung cellular damage.